Subsequent investigations of the least cardinalities of unique range set for two minimum weights over a non-Archimedean field - Banerjee, A.; Maity, S.; Banerjee, A.; Maity, S. (Institute of Mathematics, NAS of Ukraine, 2023)
UDC 517.53 First of all, we indicate a severe error in the analysis of the main results of both Chakraborty [Ukr. Math. J., 72, No. 11, 1794–1806 (2021)] and Chakraborty–Chakraborty [Ukr. Math. J., 72, No. 7, 1164–1174 (2020)], to show that both these papers cease to be true. Further, pertinent to the results of these two papers, we deal with the unique range set of a meromorphic function over a non-Archimedean field with the smallest possible weights 0 and 1 under the aegis of its most generalized form to improve the existing result.